ICT, creativity and innovation: Strategies in the configuration of environments for university learning - Veytia Bucheli, María Guadalupe; Aguirre Aguilar, Genaro; Barrios Pérez, Eduardo Gabriel (IE Revista de Investigación Educativa de la REDIECH, 2023)
Higher education demands new educational models for the integral formation of the student where the use of information and communication technologies, creative processes and innovation are present. The objective of this study is to analyze the perception of university students about the role that creativity and innovation play in the construction of their knowledge, based on the use of digital resources. The approach used was quantitative, with a descriptive transactional non-experimental design. The Digital Competence of Higher Education Students (CDAES) questionnaire was adapted for the study. Data collection was carried out through a form in Google Drive, to 150 university students, through simple random sampling. Among the main findings, aspects related to adaptation to new situations are identified, by integrating digital tools and resources that promote other types of environments, which enrich learning, promote creativity, the originality of work as a result of the effective use of ICT, where the design of educational activities allows the discovery of talent and promotes creativity in the delivery of evidence of learning.